The Relationship between education and Exclusive Breastfeeding of EmoDemo in Kotaanyar East Probolinggo 2020 - Yuliana, Wahida; Nulhakim, Bawon (STIKes Maharani Malang, 2020)
: Exclusive breastfeeding is giving breast milk to babies from birth to 6 months of age without additional food or drink except for vitamins, mineral supplements and medicines. the Indonesian government is targeting exclusive breastfeeding coverage of 80%. Based on the Basic Health Research (Riskesda) in 2018, it was found that 37.35% of mothers gave exclusive breastfeeding.. The purpose of this study was to find out whether there is a relationship between education and exclusive breastfeeding of EmoDemo participants Method: This research was conducted in March 2020. This type of research is quantitative with a cross sectional analytic approach. The sampling technique with a total sampling of 45 respondents. The data collection technique used a questionnaire in the form of a Guttman scale consisting of 10 questions. Methods of data analysis using the chi-square statistical test and obtained chi square with significant value p value 0.05. Results and Analysis: The results showed that there was a relationship between education (p-value = 0.002 Exclusive breastfeeding for mothers.The conclusion of the study is that there is the Relationship between Education and Exclusive Breastfeeding of EmoDemo Participants. Discussion: It is hoped that there will be increased support from health workers and work superiors related to the implementation of exclusive breastfeeding so that the success of exclusive breastfeeding for working mothers will increase.